Association of meleanocortin 4 receptor gene polymorphism (MC4R:C.92C>T) with feline diabetes. - Morkūnienė, Kristina; Dambrauskaitė, Justina; Bižienė, Renata; Mišeikienė, Ramutė; Pečiulaitienė , Nijolė; Kučinskas, Laimutis; Dudonytė, Ugnė (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Diabetes mellitus (DM) is a prevalent endocrine condition found in cats. Recent research has identified a connection between a higher risk of diabetes in cats and genetic factors. This genetic susceptibility to type 2 diabetes is associated with genes that control insulin secretion and function, as well as those that impact factors like obesity. The purpose of the study was to determine the prevalence of the melanocortin 4 receptor (MC4R) gene missense mutation among cats and to investigate the relationship between body condition score (BCS) and the occurrence of diabetes in felines. Materials and Methods: Genotype analysis was done for 45 samples. The research results were obtained with the polymerase chain reaction-restriction fragment length polymorphism (PCRRFLP) method. The 1,200-bp PCR product was cut with BstOI restriction enzyme. Results: Upon analyzing the data, it was found that 37.8% (n = 17) of the subjects carried the MC4R gene mutation. Across the entire population of cats studied, the C allele associated with the mutation was most prevalent in the group of cats with DM (frequency of 0.3) and least common among the clinically healthy cats (frequency of 0.2). Conclusion: After analysis of the study results, a statistically significant difference was observed between cats with DM and clinically healthy cats in the comparison of their BCS (p < 0.05). The association of the MC4R gene polymorphism with overweight and the development of diabetes has been identified. J. Adv. Vet. Anim. Res., 11(3): 738-745, September 2024 http://doi.org/10.5455/javar.2024.k825